ANALISIS DAN PERANCANGAN GAME EDUKASI BAHASA ASING UNTUK PERANGKAT ANDROID - Supriyanto Karya (Jurnal Informatika dan Bisnis, 2014)
In Indonesia today, the use of foreign languages in the world of work or education has been very common. But sometimes there are some obstacles that make it difficult to learn a foreign language, either for lack of time, not interested in the way of teaching and so on. Educational game is a game that is not only interesting to play but also has an education side for player. Game is created with the help of IntelXDK program, which can convert a gmae made in HTML5 coding into an Android application. Data was collected through secondary data from various survey from various jurnal and website. Moreover, the authors also examine various examples of similar educational games from different sources. Based on data collected by the author, as well as examples of existing HTML5 based games, the authors then make a design for display, database, and program flow. The design here is a display that can be accessed by the user. The database is designed based on what the game needed. As well as the flow of the program that is designed after looking at various examples of other existing games. Based on all the above, the writer can conclude that, an educational game, shall have the element of fun, like a lot of interaction, and audio, so that player can having fun while learning.